Design of SPECT for BNCT to measure local boron dose with GAGG scintillator. (March 2022) - Murata, Isao; Kusaka, Sachie; Minami, Kentaro; Saraue, Nobuhide; Tamaki, Shingo; Kato, Itsuro; Sato, Fuminobu
Abstract: Boron Neutron Capture Therapy (BNCT) is a promising cancer therapy, which has recently been in practical use in Japan especially using an accelerator. In BNCT real-time measurement of local boron dose is required. In the present study, a novel design of a SPECT system for BNCT (BNCT-SPECT) has been carried out to realize estimation of the local boron dose, i.e., treatment effect of BNCT. Necessary performance which BNCT community requires includes accuracy of 5% and spatial resolution of 5 mm, which are regarded to be difficult to realize. A possible design was investigated to meet the requirements. The design results we achieved are as follows: As for the elemental detection device, GAGG (3.5 × 3.5 × 30 mm 3 ) was selected, and for the collimator, the collimator hole diameter was 3.5 mm, the collimator hole pitch was 4 mm and the collimator length was 26 cm. For the obtained performance with the design, the accuracy was 4.4% and the spatial resolution was 5.1 mm. Currently prior to production of the real system, a prototype of BNCT-SPECT is being developed to acquire real projection data to confirm the performance and examine our own image reconstruction method with the obtained projection data. Highlights: Boron Neutron Capture Therapy (BNCT) is a promising radiation therapy for cancer. A novel SPECT system for BNCT (BNCT-SPECT) is required to monitor local boron dose in real-time. Design of BNCT-SPECT was completed to meet the requirements of measuring accuracy of 5% and spatial resolution of 5 mm. The obtained design performance is 4.4% of the accuracy and 5.1 mm of the spatial resolution.